Birds of a feather : bowerbirds and me - Roth, Susan L., ....- (New York : Neal Porter Books, 2019)
One makes colorful paper collages, the other, intricate environments out of found objects. And yet Susan L. Roth shows that she and the remarkable bowerbird are truly birds of a feather.
Keywords: Collage